Contamination of µCMM stylus tips: on-machine inspection - Feng, Xiaobing; Lacorne, Cyril; Fernandes, Gustavo Q.; Lawes, Simon; Kinnell, Peter (2016)
Contamination adhered to the surface of a µCMM stylus tip significantly impairs the dimensional accuracy of a µCMM system. Regular cleaning of the stylus is essential to minimising the dimensional error but little data exists for determining appropriate cleaning intervals. This study investigates the build-up of contamination on the µCMM stylus tip during probing procedures. Experiments were conducted on surfaces with controlled contamination for 18 different conditions to study the impact of surface morphology and contact pressure. Quantitative results showed that surface texture due to the difference in machining processes was more influential than surface roughness in determining contamination rate, and that higher contact pressure led to greater contamination. However, contamination rate was observed to vary significantly, suggesting a probabilistic mechanism for contamination adhesion. As such, predictive methods may not offer a reliable threshold for determining cleaning intervals. To that end, a technique for on-machine imaging has been proposed to work in-line with the µCMM and inspect surface contamination as it builds. Using epi-illuminated optical microscopy with focus stacking, debris of less than 300 nm in size was detectable.